2014
DOI: 10.1093/mnras/stu1849
|View full text |Cite
|
Sign up to set email alerts
|

Milky Way mass constraints from the Galactic satellite gap

Abstract: We use the distribution of maximum circular velocities, V max , of satellites in the Milky Way (MW) to constrain the virial mass, M 200 , of the Galactic halo under an assumed prior of a ΛCDM universe. This is done by analysing the subhalo populations of a large sample of halos found in the Millennium II cosmological simulation. The observation that the MW has at most three subhalos with V max 30 km/s requires a halo mass M 200 1.4 × 10 12 M , while the existence of the Magellanic Clouds (assumed to have V max… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 71 publications
10
64
0
Order By: Relevance
“…The green and blue dotted lines in Fig. 4 respectively indicate where N sub = 60 is realized for M halo = 10 12 M /h and M halo = 3 · 10 12 M /h; these values for the MW halo mass roughly correspond to the current observational limits [63,64]. For M halo = 10 12 M /h, even with the pure CDM case the satellite number is as low as N sub = 94, indicating that the missing satellite problem itself is ameliorated if the MW halo mass takes a value close to its lower bound.…”
Section: Implications For the Number Of Milky Way Satellitessupporting
confidence: 73%
“…The green and blue dotted lines in Fig. 4 respectively indicate where N sub = 60 is realized for M halo = 10 12 M /h and M halo = 3 · 10 12 M /h; these values for the MW halo mass roughly correspond to the current observational limits [63,64]. For M halo = 10 12 M /h, even with the pure CDM case the satellite number is as low as N sub = 94, indicating that the missing satellite problem itself is ameliorated if the MW halo mass takes a value close to its lower bound.…”
Section: Implications For the Number Of Milky Way Satellitessupporting
confidence: 73%
“…Such a lower chance is also observationally supported (Liu et al 2011). Thus the occurrence of the Magellanic Clouds and avoidance of more than three subhaloes with Vmax > 25km/s together can put a strong constraints on the MW mass (Cautun et al 2014).…”
Section: Introductionmentioning
confidence: 58%
“…Cautun et al (2014) found that the probability of having such a wide gap in velocity space is about 1% in the CDM model. Jiang & van den Bosch (2016) find the probability is even lower as 0.1% using a monte-carlo method.…”
Section: Introductionmentioning
confidence: 96%
“…For CDM the EvoFb model slightly overpredicts the number of the faintest satellites (MV > −8), but here the data could be incomplete. However, since the number of satellites scales with the host halo mass (Wang et al 2012;Cautun et al 2014), our sterile neutrino models would be increasingly in conflict with the observed luminosity functions for M host halo 10 12 M . For example, if M host halo 7 × 10 11 M , both the L6 = 700 and L6 = 12 EvoFb models would be ruled out because they fail to form enough faint satellites with MV > −10 even after accounting for the large scatter.…”
Section: Satellites Of the Milky Waymentioning
confidence: 86%